2022
DOI: 10.3389/fnagi.2021.762907
|View full text |Cite
|
Sign up to set email alerts
|

The Neuropsychiatric Changes After COVID-19 Quarantine in Patients With Cognitive Impairment and Their Caregivers in Chongqing, China: A Cohort Study

Abstract: BackgroundThe follow-up study on neuropsychiatric changes after the lifting of coronavirus disease 2019 (COVID-19) quarantine in patients with cognitive impairment and their caregivers is still lacking, and relative information is needed to formulate more comprehensive healthcare prevention measures worldwide.AimsTo provide data on the changes in neuropsychiatric performance after the lifting of COVID-19 quarantine in patients with cognitive disorders and their caregivers.MethodsTwo surveys in Chongqing, China… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
1
0
0
Order By: Relevance
“…The results of this study revealed a high CG burden, a high prevalence of depression in CGs, the development of NPS and functional dependency in PwD, and the CG-burden-related factors during the COVID-19 outbreak. The findings are in accordance with previous reports of a rising CG burden and worsening NPS during the pandemic (Borelli et al, 2021; Cohen et al, 2020; Tsapanou et al, 2021; Yuan et al, 2022). In this study, the authors showed the association between CG burden and related factors, including CG depression, a high level of CG education, conflict between the CGs and the PwD, and a high score for NPS.…”
Section: Discussionsupporting
confidence: 93%
“…The results of this study revealed a high CG burden, a high prevalence of depression in CGs, the development of NPS and functional dependency in PwD, and the CG-burden-related factors during the COVID-19 outbreak. The findings are in accordance with previous reports of a rising CG burden and worsening NPS during the pandemic (Borelli et al, 2021; Cohen et al, 2020; Tsapanou et al, 2021; Yuan et al, 2022). In this study, the authors showed the association between CG burden and related factors, including CG depression, a high level of CG education, conflict between the CGs and the PwD, and a high score for NPS.…”
Section: Discussionsupporting
confidence: 93%